Impact of endoscopic biopsy surveillance of Barrett's oesophagus on pathological stage and clinical outcome of Barrett's carcinoma. Issue 2 (1st August 1998) - van Sandick, J W; van Lanschot, J J B; Kuiken, B W; Tytgat, G N J; Offerhaus, G J A; Obertop, H
Abstract : Background —The efficacy of endoscopic biopsy surveillance of Barrett's oesophagus in reducing mortality from oesophageal cancer has not been confirmed. Aims —To investigate the impact of endoscopic biopsy surveillance on pathological stage and clinical outcome of Barrett's carcinoma. Methods —A clinicopathological comparison was made between patients who initially presented with oesophageal adenocarcinoma (n=54), and those in whom the cancer had been detected during surveillance of Barrett's oesophagus (n=16). Results —The surveyed patients were known to have Barrett's oesophagus for a median period of 42 months (range 6–144 months). Prior to the detection of adenocarcinoma or high grade dysplasia, 13 of 16 patients (81%) were previously found to have low grade dysplasia. Surgical pathology showed that surveyed patients had significantly earlier stages than non-surveyed patients (p=0.0001). Only one surveyed patient (6%) versus 34 non-surveyed patients (63%) had nodal involvement (p=0.0001). Two year survival was 85.9% for surveyed patients and 43.3% for non-surveyed patients (p=0.0029). Conclusions —The temporal course of histological progression in our surveyed patients supports the theory that adenocarcinoma in Barrett's oesophagus develops through stages of increasing severity of dysplasia. Endoscopic biopsy surveillance of Barrett's oesophagus permits detection of malignancy at an early and curable stage, thereby potentially reducing mortality from oesophageal adenocarcinoma.